Feedback in action within bedside teaching encounters: a video ethnographic study. Issue 9 (September 2014) - Rizan, Chantelle; Elsey, Christopher; Lemon, Thomas; Grant, Andrew; Monrouxe, Lynn V
<x xml:space="preserve">Abstract</x> Discuss ideas arising from the article at 'discuss'